The fall-out from Brexit - Young, Stuart; Antill, Peter D.; Fisher, Richard (Trident Publications Ltd, 2017)
On 23rd June 2016, the British electorate voted to leave the European Union (EU) [i], in what can only be described as a surprise result that has sent shockwaves through not only the British political establishment but across both Europe and the world. As far as UK defence acquisition was concerned, a strategic environment that was already in a state of dynamic flux due to the publication of a new National Security Strategy (NSS) and Strategic Defence and Security Review (SDSR) in late 2015, was made even more complex by the referendum result and what that could mean for the UK's international relations. While the full impact of the Brexit vote is unlikely to be understood for some time to come – especially as the UK has yet to officially declare its intention to leave under Article 50 of the Lisbon Treaty – this article will look at some of issues and challenges that now face UK defence acquisition, in light of recent political events.